Katalogizacijski standard Resource description and access (RDA) - Petek, Marija (Knjižnica, 2017)
Purpose: This article deals with the cataloguing standard Resource Description and Access (RDA) that replaces the second edition of Anglo-American Cataloguing Rules (AACR2). Its historical background, development, influence of AACR2 is presented as well as underlying IFLA conceptual model, cataloguing principles and international standard bibliographic description. A comparison is made between the RDA and the local cataloguing code Pravilnik i priručnik za izradbu abecednih kataloga (PPIAK). Methodology/approach: Objects and principles of RDA, its structure, a set of core elements and new elements indicating content, media and carrier are described and compared with current cataloguing practice, some differences are illustrated by examples. Results: There are many differences between RDA and PPIAK: RDA being a content-only standard, the ISBD punctuaction and order of areas is not required, no abbreviations are used etc. But, considering some aspects RDA continues traditional cataloguing. Research limitation: Due to extensiveness of the RDA text only the most significant characteristics and changes are described. Originality/practical implications: This is the first article about RDA in Slovenian.
Keywords: cataloguing; katalogizacija; RDA; bibliographic description; access point; bibliografski opis; users; točke dostopa; uporabniki